Co-Application of Seaweed Extract (Solieria filiformis) and Silicon: Effect on Sporulation, Mycorrhizal Colonization, and Initial Growth of Mimosa caesalpiniaefolia - Isaac Alves da Silva; José Lucas Sousa de Andrade; Francisco Luan Almeida Barbosa; Murilo de Sousa Almeida; Marjory Lima Holanda Araújo; Adijailton Jose de Souza; Ademir Sergio Ferreira Araujo; Arthur Prudêncio de Araujo Pereira; Kaio Gráculo Vieira Garcia (Microorganisms)
Seaweed extracts (SEs) and silicon (Si) are known to enhance plant growth under adverse conditions. However, their combined effects on arbuscular mycorrhizal fungi (AMF) are not yet fully understood. This study evaluated the effect of the co-application of an SE and Si on the AMF spore abundance, mycorrhizal colonization, and early growth of Mimosa caesalpiniaefolia. Plants were grown in a greenhouse for 70 days in soil with or without an SE (Solieria filiformis) and three Si levels (0, 150, and 300 mg kg−1). Growth parameters, AMF spore abundance, mycorrhizal colonization, and plant/soil chemical composition were assessed. SE and Si increased the plant height, stem diameter, number of leaves, and shoot dry mass, while higher Si levels reduced the root dry mass and length. Mycorrhizal colonization was highest (64%) at 150 mg kg−1 Si with SE, whereas AMF spore abundance decreased as Si increased. SE and 300 mg kg−1 Si raised the Si levels in the shoot, while root Si increased only at 300 mg kg−1 Si. Shoot Na increased at 300 mg kg−1 Si without SE, whereas K was highest at 150 mg kg−1 Si with SE. The soil pH, electrical conductivity, and Na increased at 300 mg kg−1 Si, while K and P decreased at this level without SE. These findings indicate that SE and Si co-application benefits early growth and may modulate mycorrhizal symbiosis, highlighting the importance of proper management to maximize plant and soil benefits.